2005
DOI: 10.1073/pnas.0504211102
|View full text |Cite
|
Sign up to set email alerts
|

A role for the Tip60 histone acetyltransferase in the acetylation and activation of ATM

Abstract: FATC domain ͉ TRRAP ͉ NuA4 ͉ chromatin remodeling T he product of the ataxia telangiectasia (AT) gene, the AT mutant (ATM) protein kinase, is a key component of the signal-transduction pathway activated by DNA damage (1). In response to DNA strand breaks, ATM's kinase activity is upregulated, and ATM becomes autophosphorylated on Ser 1981 (2). ATM autophosphorylation initiates the conversion of the inactive ATM dimer to an active, monomeric ATM. ATM then phosphorylates multiple proteins involved in the DNA dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
667
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(695 citation statements)
references
References 35 publications
25
667
3
Order By: Relevance
“…Sumoylation promotes TIP60 HAT activity in response to UV irradiation Since TIP60 is sumoylated in response to UV irradiation ( Figure 2) and its HAT activity is activated by DNA damage (Sun et al, 2005), we tested whether the sumoylation modulates its HAT activity using histone-2A acetylation as a reporter (Yamamoto and Horikoshi, 1997). As shown in Figure 6a, the level of histone-2A acetylation is increased in cells expressing GFP-TIP60 with the highest level observed in cells expressing SUMO-TIP60dm.…”
Section: Uv Irradiation Induces the Sumoylation Of Tip60 At Lysines 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Sumoylation promotes TIP60 HAT activity in response to UV irradiation Since TIP60 is sumoylated in response to UV irradiation ( Figure 2) and its HAT activity is activated by DNA damage (Sun et al, 2005), we tested whether the sumoylation modulates its HAT activity using histone-2A acetylation as a reporter (Yamamoto and Horikoshi, 1997). As shown in Figure 6a, the level of histone-2A acetylation is increased in cells expressing GFP-TIP60 with the highest level observed in cells expressing SUMO-TIP60dm.…”
Section: Uv Irradiation Induces the Sumoylation Of Tip60 At Lysines 4mentioning
confidence: 99%
“…Like p53, TIP60 accumulates in response to DNA damage (for example, Legube et al, 2004). Suppression of TIP60 blocks ATM activation and ATM-dependent phosphorylation of p53, suggesting that TIP60 is an upstream molecule in ATMdependent DNA damage response (Sun et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, protein phosphatases have also been shown to play a role in ATM activation (Ali et al, 2004;Goodarzi et al, 2004). DNA-damaged-induced acetylation of ATM has been reported by Sun et al (2005) and this was shown to run in parallel with pS1981 after radiation exposure. They identified the Tip60 histone acetyltransferase as the enzyme responsible and revealed that a dominant negative form of Tip60 reduced both acetylation and autophosphorylation of ATM.…”
Section: Perspectivementioning
confidence: 89%
“…Price and co-workers showed that ATM is acetylated by the Tip60 complex after DNA damage and that disruption of Tip60 by siRNA causes defects in ATM autophosphorylation, suggesting that the activity of Tip60 is required for ATM autophosphorylation (Sun et al, 2005(Sun et al, , 2006. They also showed that Tip60 is required for ATM-dependent phosphorylation of p53 and Chk2 in bleomycin-treated cells and interacts with the C-terminal FATC domain on ATM.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 99%